Ingestion of an ample amount of meat substitute based on a lysine-enriched, plant-based protein blend stimulates postprandial muscle protein synthesis to a similar extent as an isonitrogenous amount of chicken in healthy, young men. Issue 10 (28th November 2022) - Kouw, Imre W.K.; Pinckaers, Philippe J.M.; Le Bourgot, Cindy; van Kranenburg, Janneau M.X.; Zorenc, Antoine H.; de Groot, Lisette C.P.G.M.; Verdijk, Lex; Snijders, Tim; van Loon, Luc J.C.
Abstract: Plant-based proteins are considered to be less effective in their capacity to stimulate muscle protein synthesis when compared with animal-based protein sources, likely due to differences in amino acid contents. We compared the postprandial muscle protein synthetic response following the ingestion of a lysine-enriched plant-based protein product with an isonitrogenous amount of chicken. Twenty-four men (age 24 ± 5 years; BMI 22·9 ± 2·6 kg·m −2 ) participated in this parallel, double-blind, randomised controlled trial and consumed 40 g of protein as a lysine-enriched wheat and chickpea protein product (Plant, n 12) or chicken breast fillet (Chicken, n 12). Primed, continuous intravenous l -(ring- 13 C6 )-phenylalanine infusions were applied while repeated blood and muscle samples were collected over a 5-h postprandial period to assess plasma amino acid responses, muscle protein synthesis rates and muscle anabolic signalling responses. Postprandial plasma leucine and essential amino acid concentrations were higher following Chicken ( P < 0·001), while plasma lysine concentrations were higher throughout in Plant ( P < 0·001). Total plasma amino acid concentrations did not differ between interventions ( P = 0·181). Ingestion of both Plant and Chicken increased muscle protein synthesis rates from post-absorptive: 0·031 ± 0·011 and 0·031 ± 0·013 to postprandial: 0·046 ± 0·010 and 0·055 ± 0·015 % h −1, respectively ( P -time < 0·001), with no differences between Plant and Chicken (time x treatment P = 0·068). Ingestion of 40 g of protein in the form of a lysine-enriched plant-based protein product increases muscle protein synthesis rates to a similar extent as an isonitrogenous amount of chicken in healthy, young men. Plant-based protein products sold as meat replacers may be as effective as animal-based protein sources to stimulate postprandial muscle protein synthesis rates in healthy, young individuals.